Age-period-cohort analysis of disease burden of depressive disorders in the Chinese population - Wang Ying; Hou Yuwei; Zhang Zhe (Sichuan jingshen weisheng, 2025)
BackgroundMental health issues have become increasingly prominent amid rising societal pressure. Depressive disorders， characterized as chronic and recurrent conditions， adversely affect patients' physical and mental well-being while imposing a significant economic burden. Previous studies on depressive disorders in China have relied on cross-sectional surveys， capturing prevalence at specific time points， but lacking systematic analyses across age， period， and cohort dimensions.ObjectiveTo analyze long-term trends in the disease burden of depressive disorder in the Chinese population from 1990 to 2021， and to provide references to inform prevention and treatment strategies.MethodsData on the disease burden of depressive disorders in China were obtained from the Global Burden of Disease Study 2021 （GBD 2021） database. A joinpoint regression model was used to analyze trends in the disease burden. An age-period-cohort model， implemented in Stata 17.0， was applied to assess variations in incidence and disease burden attributable to age， period and cohort effects.ResultsFrom 1990 to 2021， the disability-adjusted life year （DALY） rate for depressive disorders in China decreased by an average of 0.27% annually， while the incidence rate decreased by an average of 0.24% annually. Females had higher incidence and DALY rates than those of males. The age-period-cohort model analysis revealed that age effects on incidence and disease burden steadily increased， period effects declined over time， and cohort effects initially increased and then declined.ConclusionFrom 1990 to 2021， both the incidence and DALY rates of depressive disorders in China showed a declining trend. Females experienced a higher burden compare to males. Additionally， incidence and DALY rates increased with age but declined over time.